PCSK9 and lipoprotein (a) levels are two predictors of coronary artery calcification in asymptomatic patients with familial hypercholesterolemia. (November 2016) - Alonso, Rodrigo; Mata, Pedro; Muñiz, Ovidio; Fuentes-Jimenez, Francisco; Díaz, Jose Luis; Zambón, Daniel; Tomás, Marta; Martin, Cesar; Moyon, Thomas; Croyal, Mikaël; Thedrez, Aurélie; Lambert, Gilles
Abstract: Background and aims: We aimed to assess whether elevated PCSK9 and lipoprotein (a) [Lp(a)] levels associate with coronary artery calcification (CAC), a good marker of atherosclerosis burden, in asymptomatic familial hypercholesterolemia. Methods: We selected 161 molecularly defined FH patients treated with stable doses of statins for more than a year. CAC was measured using the Agatston method and quantified as categorical variable. Fasting plasma samples were collected and analyzed for lipids and lipoproteins. PCSK9 was measured by ELISA, Lp(a) and apolipoprotein (a) concentrations by inmunoturbidimetry and LC-MS/MS, respectively. Results: Circulating PCSK9 levels were significantly reduced in patients without CAC (n = 63), compared to those with CAC (n = 99). Patients with the highest CAC scores (above 100) had the highest levels of circulating PCSK9 and Lp(a). In multivariable regression analyses, the main predictors for a positive CAC score was age and sex followed by circulating PCSK9 and Lp(a) levels. Conclusions: In statin treated asymptomatic FH patients, elevated PCSK9 and Lp(a) levels are independently associated with the presence and severity of CAC, a good predictor of coronary artery disease. Highlights: Factors besides LDL may determine why some patients with familial hypercholesterolemia develop CAD earlier in life than others. We correlated coronary artery calcifications with PCSK9 and Lp(a) levels in 161 asymptomatic patients with molecular diagnosis of FH. We report that both PCSK9 and Lp(a) are independently predictive of elevated coronary artery calcium scores, an excellent marker of atherosclerotic burden.